MODIFIKASI ASPAL KERAS STANDAR DENGAN BITUMEN ASBUTON HASIL EKSTRAKSI - Kurniadji Kurniadji (Direktorat Bina Teknik Jalan dan Jembatan, 2008)
The recent issues of a road asphalt work in Indonesia is unreachable of design life, because of premature road deterioration, type of it are rutting and plastic deformation especially happens to the location with the high temperature (About 70 degree Celsius), which is resulted from improper used of asphalt on supporting traffic load. It happened cause of using unsuitable asphalt in high temperature with low penetration index(PI) and low performance grade (PG ). To maximize PI and PG value, extracted asbuton bitumen used as atrial based on equality of available references, blended of asphalt cement pen 60 with asbuton bitumen obviously rose not only PI value from -1.01 of asbuton bitumen to +0.61 of 100% asbuton bitumen, but also PG from 56 to PG 95 of 100%. Actually, PG 72 and PI = 0 which was gained from combination of 31.2% asbuton bitumen and 68.8% standard asphalt cement is quite suitable to use in our country. On variation comparison of asbuton bitumen and standard asphalt cement above resulting stiff value of bitumen 16.4 MPa and stiffness of mixture 3707 MPa of preliminary bitumen value 0% each 9.5 MPa and 3155 MPa. Stiffness blended asphalt extent the design life from 4.26 years to 5.61 years. Keyword: Penetration Index, Performance Grade, Asbuton, Stiffness